Crosstalk between IL‐15Rα+ tumor‐associated macrophages and breast cancer cells reduces CD8+ T cell recruitment. Issue 6 (25th May 2022) - Zhang, Wenlong; Zhang, Qing; Yang, Nanfei; Shi, Qian; Su, Huifang; Lin, Tingsheng; He, Zhonglei; Wang, Wenxin; Guo, Hongqian; Shen, Pingping
Abstract: Background: Interleukin‐15 (IL‐15) is a promising immunotherapeutic agent owing to its powerful immune‐activating effects. However, the clinical benefits of these treatments are limited. Crosstalk between tumor cells and immune cells plays an important role in immune escape and immunotherapy drug resistance. Herein, this study aimed to obtain in‐depth understanding of crosstalk in the tumor microenvironment for providing potential therapeutic strategies to prevent tumor progression. Methods: T‐cell killing assays and co‐culture models were developed to determine the role of crosstalk between macrophages and tumor cells in breast cancer resistant to IL‐15. Western blotting, histological analysis, CRISPR‐Cas9 knockout, multi‐parameter flow cytometry, and tumor cell‐macrophage co‐injection mouse models were developed to examine the mechanism by which IL‐15Rα + tumor‐associated macrophages (TAMs) regulate breast cancer cell resistance to IL‐15. Results: We found that macrophages contributed to the resistance of tumor cells to IL‐15, and tumor cells induced macrophages to express high levels of the α subunit of the IL‐15 receptor (IL‐15Rα). Further investigation showed that IL‐15Rα + TAMs reduced the protein levels of chemokine CX3C chemokine ligand 1 (CX3CL1) in tumor cells to inhibit the recruitment of CD8 + T cells by releasing the IL‐15/IL‐15Rα complex (IL‐15Rc). Administration of an IL‐15Rc blocking peptide markedly suppressed breast tumor growth and overcame the resistance of cancer cells to anti‐ programmed cell death protein 1 (PD‐1) antibody immunotherapy. Interestingly, Granulocyte‐macrophage colony‐stimulating factor (GMCSF) induced γ chain (γc) expression to promote tumor cell‐macrophage crosstalk, which facilitated tumor resistance to IL‐15. Additionally, we observed that the non‐transcriptional regulatory function of hypoxia inducible factor‐1alpha (HIF‐1α) was essential for IL‐15Rc to regulate CX3CL1 expression in tumor cells. Conclusions: The IL‐15Rc‐HIF‐1α‐CX3CL1 signaling pathway serves as a crosstalk between macrophages and tumor cells in the tumor microenvironment of breast cancer. Targeting this pathway may provide a potential therapeutic strategy for enhancing the efficacy of cancer immunotherapy.